THE USE OF THE INTERACTIVE BOARD AT ENGLISH LESSONS (International relations and international law Journal, 2016)
The author investigates in article the use of an interactive board at English lessons which carries out functions of the active screen for demonstration the presentations, text documents, drawings, movies, etc.
Keywords: English; interactive board